2000
DOI: 10.1063/1.126181
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of silicon oxidation rate due to tensile mechanical stress

Abstract: Oxidation of silicon wafers under external mechanical stress was studied in this work. From the oxide thickness profile measured by an automatic ellipsometer, it was found that the oxidation kinetics of silicon was affected by the mechanical stress. The tensile stress strongly enhances the oxidation rate of silicon. A concept was proposed to explain this phenomenon by using a well-known physical Si–SiO2 lattice model. The tensile stress in the silicon will enlarge the atom spacing of silicon and make the oxida… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
43
1

Year Published

2001
2001
2020
2020

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 20 publications
1
43
1
Order By: Relevance
“…5(a). The predicted curve agrees well with the experimental data provided by Tamura et al 31 Moreover, experimental results by Hwu et al 33,34 and Kao et al 7,29 also indicated that tensile loads accelerated the silicon oxidation process while compressive load retarded it. However, since the aim of their experiments was to investigate the non-uniform oxidation behavior of two-dimensional silicon specimens, it is hard to compare their results and the present prediction results directly.…”
Section: B Effect Of Constant Strain On Oxide Stress and Scale Thicksupporting
confidence: 81%
See 1 more Smart Citation
“…5(a). The predicted curve agrees well with the experimental data provided by Tamura et al 31 Moreover, experimental results by Hwu et al 33,34 and Kao et al 7,29 also indicated that tensile loads accelerated the silicon oxidation process while compressive load retarded it. However, since the aim of their experiments was to investigate the non-uniform oxidation behavior of two-dimensional silicon specimens, it is hard to compare their results and the present prediction results directly.…”
Section: B Effect Of Constant Strain On Oxide Stress and Scale Thicksupporting
confidence: 81%
“…31,32 In the third category, the effect of external loads on the oxidation behavior of silicon was considered. Yen et al 33,34 placed two silicon wafers vertically at one side and put a small slice of quartz across the middle of the wafers to make them bend. However, although the bending deformation of the samples remained constant, the bending moment would diminish with time due to creep deformation.…”
Section: Introductionmentioning
confidence: 99%
“…At the same time, considerable effort has been invested in manipulating Si oxidation kinetics. For example, uni-and biaxial strains have been used in manufacturing Si-based devices, taking advantage of the fact that tensile stress increases the overall oxidation rate of thermally grown oxides (5).…”
mentioning
confidence: 99%
“…In cases of stressed oxidation, as with SiC fiber tows used to reinforce CMCs, the oxidation rate is significantly affected by the presence of the stress. For tensile stresses, the rate increases [125,199,200], whereas compressive stresses tend to decrease the rate. This is due, in part, to the effect of stress on crack growth.…”
Section: Oxidation In Air and Silicic Acid-saturated Steammentioning
confidence: 99%
“…Yen and Hwu [199,200] found that tensile stress strongly enhances the oxidation rate of silicon and that the parabolic rate constant was stress dependent. Hay noted that SiC oxidation is very similar to that of silicon [142].…”
Section: Oxidation In Air and Silicic Acid-saturated Steammentioning
confidence: 99%